EFEKTIFITAS METODE AL-MIFTAH DALAM MENINGKATKAN KEMAMPUAN MEMBACA KITAB KUNING SANTRI - Khoridatul Bahiyah; M. Jadid Khadavi (LPPM STAI Muhammadiyah Probolinggo, 2024)
The research objective in this study is to review the effectiveness of the al-Miftah method in improving the ability to read the yellow book for students at the Sullamul Hidayah Islamic boarding school in Probolinggo. In this study, researchers conducted research using a qualitative approach, while the type of research used was a case study that explored real life. The sources of data and information obtained in this research were from observations and interviews with several parties concerned. The results of research at the Sullamul Hidayah Islamic Boarding School show that this method is very influential and effective for new students who will start the basic science of reading the yellow book, namely the science of nahwu and sharaf. The effectiveness of the al-Miftah method at the Sullamul Hidayah Islamic Boarding School is that it provides a guarantee that within one year the students at the Sullamul Hidayah Islamic Boarding School have the ability to read the yellow book well according to the rules. Apart from that, it also has a positive impact on the quality of Islamic boarding schools which have proven successful in winning yellow book reading competitions at the sub-district and district levels.